Dapatkah Pengungkapan Tanggung Jawab Sosial Memoderasi Pengaruh Koneksi Politik dan Kepemilikan Manajerial Terhadap Agresivitas Pajak? - Sumingtio, Andre; Trisnawati, Estralita; Firmansyah, Amrie (E-Jurnal Akuntansi, 2022)
The political connections owned by the company become the motivation to carry out tax aggressiveness by reducing political costs and choosing parties who have special affinity with the government. The purpose of this study was to determine the effect of political connections, managerial ownership and disclosure of governance on tax aggressiveness with disclosure of social responsibility as a moderating variable. The research data uses non-consumer goods sector companies listed on the Indonesia Stock Exchange for the 2016-2019 period and obtained a total of 148 observations. The data analysis tool used is Wrap Partial Least Square (PLS) 7.0 software. Based on the results of the study, it is known that the moderating variable of social responsibility disclosure is able to moderate the effect of political connections and managerial ownership, and managerial ownership on tax aggressiveness. Keywords: Tax Aggressiveness; Political Connections; Managerial Ownership; Good Corporate Governance; Corporate Social Responsibility.